Психологічна особливість сформованості ставлення до материнства жінок, які мають перших дітей до 3-х років - Підчасов, Є. В.; Pidchasov, Ye. V.; ORCID: https://orcid.org/0000-0001-5057-4828; Чепелєва, Н. І.; Chepelieva, N. I.; ORCID: https://orcid.org/0000-0003-2101-9571 (Науковий вісник Ужгородського національного університету. Серія: Психологія. – 2022. – Вип. 3. – С. 35-39, 2022)
Розглянуто феномен материнства та рoлі матері як складової жіночої Я-концепції. Материнство є одним із найбільш насичених та довготривалих періодів життя жінки. З появою вже власної дитини у подружжя, в сімейній структурі відбуваються суттєві зміни як у соціальній так і у психологічній сферах. Ставлення жінки до материнства формується в процесі низки різнобічних цілеспрямованих психологічних впливів на особистість, результатом чого є сформована готовність до народження та виховання дитини. Перевірено емпірично сформованість рівня ставлення до материнства через певний час після народження дитини, коли «ламаються» ряд ідеалізованих установок і стереотипів. Розкрито розвиток сімейної системи і дію материнських стереотипів, в тому числі певних ідеальних уявлень, які трансформуються з урахуванням реальної ситуації і проявляється в тому, що на фоні позитивності уявлень переважає помірність у ставленні до власної материнської ролі.

The article examines the phenomenon of motherhood and the role of the mother as a component of the female selfconcept. Motherhood is one of the most intense and long-lasting periods of a woman's life. With the appearance of their own child in the couple, significant changes occur in the family structure in both social and psychological spheres. A woman's attitude to motherhood is formed in the process of a number of multifaceted targeted psychological influences on the personality, the result of which is the formed readiness for the birth and upbringing of a child. It is possible to check the empirically formed level of attitude towards motherhood most objectively after a certain time after the birth of a child, when a number of idealized attitudes and stereotypes "break", which became the goal of this study. The preliminary results confirmed some common features of the sample of mothers of first children up to 3 years of age, which made it possible to distinguish them into a separate subgroup, which demonstrates the similarity of views and characteristics of attitudes. The results of the performed theoretical and empirical analysis testify to the richness of the parameters of mother-child interaction, the integration of the mother's role in all aspects of the child's life. A tendency towards the average level in all indicators of attitude towards motherhood was also revealed, which can be considered as the tendency of this sample of women to implement their motherhood with correction for the real situation in child-parent interaction. In general, women's attitude towards motherhood as a woman's role is quite positive and is perceived as a supplement and expansion of opportunities for self-realization, however, women who have become mothers for the first time do not yet have enough experience and do not yet perceive their motherhood as a higher degree of satisfaction. The article reveals the development of the family system and the effect of maternal stereotypes, including certain ideal ideas, which are transformed taking into account the real situation and is manifested in the fact that against the background of positivity of ideas, moderation prevails in the attitude to one's own maternal role.

Рассмотрен феномен материнства и роли матери как составляющей женской Я-концепции. Материнство является одним из самых насыщенных и длительных периодов жизни женщины. С появлением уже собственного ребенка у супругов, в семейной структуре происходят существенные изменения как в социальной, так и в психологической сферах. Отношение женщины к материнству формируется в процессе ряда разносторонних целенаправленных психологических воздействий на личность, результатом чего сформирована готовность к рождению и воспитанию ребенка. Проверена эмпирически сформированность уровня отношения к материнству через некоторое время после рождения ребенка, когда «ломаются» ряд идеализированных установок и стереотипов. Раскрыто развитие семейной системы и действие материнских стереотипов, в том числе определенных идеальных представлений, которые трансформируются с учетом реальной ситуации и проявляются в том, что на фоне положительности представлений преобладает умеренность по отношению к собственной материнской роли.
Psychological feature of formed attitude to maternity of women who have first children under 3 years of age
Підчасов, Є. В. Психологічна особливість сформованості ставлення до материнства жінок, які мають перших дітей до 3-х років / Підчасов Є. В., Чепелєва Н. І. // Науковий вісник Ужгородського національного університету. Серія: Психологія. – 2022. – Вип. 3. – С. 35-39. - DOI: https://doi.org/10.32782/psy-visnyk/2022.3.7.
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; материнство; motherhood; психологічна сформованість; psychological formation; психологическая сформированность; ставлення до материнства; attitude to motherhood; отношение к материнству; моделі материнства; models of motherhood; модели материнства; психологічна готовність; psychological readiness; психологическая готовность; народження дитини; виховання дитини